Treatment of vivax malaria on the western border of Thailand. - Luxemburger, C; van Vugt, M; Jonathan, S; Mcgready, R; Looareesuwan, S; White, N; Nosten, F (1999)
The efficacy of chloroquine (25 mg base/kg over 3 days) in Plasmodium vivax malaria was evaluated in 1995/96 in 342 patients living in an endemic area on the western border of Thailand. Clearance of fever and parasites was obtained within 2 days in > 95% of the patients, and all were aparasitaemic by day 4. Reappearance of P. vivax occurred in 1 patient on day 21 and in 8 by day 28, giving a 28-day cure rate of 97% [95% confidence interval (CI) 95-99%]. By day 63, the relapse/re-infection rate was 63% (95% CI 57-69%). Most reappearances of parasitaemia (85%; 121/143) were symptomatic. These patients were retreated either with chloroquine alone (n = 70) or with chloroquine and primaquine (0.25 mg/kg daily for 14 days) (n = 43). Only 1 patient (in the chloroquine-only group) had prolonged parasite clearance (D8) and he developed recurrent P. vivax by day 21 suggesting possible recrudescence. The addition of primaquine to chloroquine reduced the risk of having a third vivax episode within 2 months by 96% (95% CI 83-99%). This resulted in a significantly higher haematocrit at day 42 despite a greater decrease in haematocrit during the first week of treatment with chloroquine-primaquine (P = 0.04). Chloroquine remains highly effective on the western border of Thailand and the use of strictly supervised primaquine effectively prevents relapse. The introduction of primaquine on a large scale in an endemic area still requires a long-term risk-benefit assessment which must take into account potential toxicity, low compliance and reductions in the incidence and severity of P. falciparum infections by co-existent P. vivax.